Migration and crop change: evidence from Brazil using a spatial equilibrium model - Monteiro, Gabriel Facundes (2021)
Climate-change forecasts for Brazil points to sizable and spatially heterogeneous changes in temperature. This is likely to spur migration and spatial changes in crop patterns. We develop a unique tractable model that integrates both migration and agricultural adaptation as responses to climate change. Our model considers that workers\' locational choice is impacted by climate change through three channels: a direct amenity-value channel, as well as the indirect agricultural wages and housing prices channels. The impacts from indirect channels are affected by how farmers adapt to the new climate. Our simulations predict up to an 18.25% increase in micro-region migration rates, with barely no effect from crop change. On the other hand, agricultural adaptation has important impacts in employment in agriculture. The South macro-region is predicted to have an increase in agriculture share of employment when farmers change crop patterns, this includes a reduction in agriculture area dedicated to the production of Maize and an increase the area dedicated to Coffee in the region. Our results help to identify populations most vulnerable to climate change and the regions where most gains from agricultural adaptation may come from.